ANALISIS STANDAR PROSES DALAM PELAKSANAAN PEMBELAJARAN PPKN - Yulianti, Endang; Arafat, Yasir; Wardiah, Dessy (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2020)
The implementation of Pancasila and Citizenship Education (PPKn) in accordance with the standard of the learning process is considered to be very relevant to the current conditions, where a crisis of identity and enthusiasm for loving the motherland is a national problem today. This study aims to determine the standard process in implementing PPKn learning in elementary schools. The location of the study was conducted at Gelumbang Elementary School 2 in Muara Enim Regency. This study uses a qualitative case study method (case studies). Data collection techniques in this study used interviews, documentation, and observation. Data analysis uses qualitative techniques which consist of three stages of data analysis namely data reduction, display or presentation of data as well as drawing conclusions and data verification. The results of this study state that the facts of the learning process that includes planning, implementation, and evaluation of learning outcomes cannot be carried out thoroughly in accordance with the process standards set by the government. However, with maximum effort the learning process of PPkn can run effectively in a number of notes, namely the teacher must be more optimally managing learning.